2021
DOI: 10.1007/s40415-021-00719-7
|View full text |Cite
|
Sign up to set email alerts
|

Pollen morphology and evolutionary history of Sapindales

Abstract: In Brazil, Sapindales is represented by six families Anacardiaceae, Burseraceae, Meliaceae, Rutaceae, Sapindaceae, and Simaroubaceae. Palynological studies on its members are varied, including few detailed descriptions as well as palynotaxonomic analyses or brief diagnoses in floras or ecological, paleopalynological, or melissopalynological investigations. This study aimed to compile the main pollen characters of Sapindales families occurring in Brazil through a thorough review of the literature including nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In this family, the pollens of most genera did not have a consistent number of apertures, with most being 3–4 or 4–5 colporate. Interestingly, many Sapotaceae are pollinated or likely to be pollinated by bats (Aziz et al., 2021; Harley, 1991), including in Fiji (Scanlon, Petit, Tuiwawa, & Naikatini, 2014), as are some species in the Sapindales (Fleming et al., 2009), a group known to have genera with heteromorphic pollen (Gonçalves‐Esteves et al., 2022). Harley (1991) found that the ratio within a sample of one aperture number to the other was generally 0.25–0.30 to 0.65–0.75.…”
Section: Discussionmentioning
confidence: 99%
“…In this family, the pollens of most genera did not have a consistent number of apertures, with most being 3–4 or 4–5 colporate. Interestingly, many Sapotaceae are pollinated or likely to be pollinated by bats (Aziz et al., 2021; Harley, 1991), including in Fiji (Scanlon, Petit, Tuiwawa, & Naikatini, 2014), as are some species in the Sapindales (Fleming et al., 2009), a group known to have genera with heteromorphic pollen (Gonçalves‐Esteves et al., 2022). Harley (1991) found that the ratio within a sample of one aperture number to the other was generally 0.25–0.30 to 0.65–0.75.…”
Section: Discussionmentioning
confidence: 99%
“…The pollen morphological characteristics are typically stable, showing the common characteristics at the family, genera or specie level ( Stafford and Knapp, 2006 ; Jia et al., 2015 ; Goncalves-Esteves et al., 2021 ). Walker (1974) reported that the sculptural types of primitive type pollen are simple, and the pollen sculptural types of advanced species are complex.…”
Section: Discussionmentioning
confidence: 99%
“…Muller and Leenhouts (1976) classified the apertural types of extant Sapindaceae pollen into 12 groups and regarded the spherical tricolporate type A with long colpi and small endoapertures as a basic type. Gonçalves-Esteves et al (2021) concluded that tri(tetra)-colporate, which is most common, tri(tetra)-colporate, parasyncolporate, syncolporate or hemisyncolporate apertural types were found in Sapindaceae. Syncolporate and parasyncolporate types only occur in the subfamily Sapindoideae, and most commonly in the tribe Cupanieae (Acevedo-Rodríguez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%